Docetaxel-loaded folate-modified TPGS-transfersomes for glioblastoma multiforme treatment - Luiz, Marcela Tavares (2021)
Glioblastoma multiforme (GBM) is a first primary Central Nervous System tumor with high incidence and lethality. Its treatment is hampered by the difficulty to overcome the blood-brain barrier (BBB) and by the non-specificity of chemotherapeutics to tumor cells. This study was based on the development characterization and in vitro efficacy of folate-modified TPGS transfersomes containing docetaxel (TF-DTX-FA) to improve GBM treatment. TF-DTX-FA and unmodified transfersomes (TF-DTX) were prepared through thin-film hydration followed by extrusion technique and characterized by physicochemical and in vitro studies. All formulations showed low particles sizes (below 200 nm), polydispersity index below 0.2, negative zeta potential (between −16.75 to −12.45 mV) and high encapsulation efficiency (78.72 ± 1.29% and 75.62 ± 0.05% for TF-DTX and TF-DTX-FA, respectively). Furthermore, cytotoxicity assay of TF-DTX-FA showed the high capacity of the nanocarriers to reduce the viability of U-87 MG in both 2D and 3D culture models, when compared with DTX commercial formulation and TF-DTX. In vitro cellular uptake assay indicated the selectivity of transfersomes to tumoral cells when compared to normal cells, and the higher ability of TF-DTX-FA to be internalized into 2D U-87 MG in comparison with TF-DTX (72.10 and 62.90%, respectively, after 24 h). Moreover, TF-DTX-FA showed higher permeability into 3D U-87 MG spheroid than TF-DTX, suggesting the potential FA modulation to target treatment of GBM.